(untitled) (Scientia Agropecuaria, 2021)
The development of products for human consumption with added value from hydrobiological resources generates remnants of the raw material that are classified as co-products, by-products and solid and liquid organic waste that, if not treated, cause a negative environmental impact. The use of these remnants for agricultural purposes is a reason for research because they have bioactive compounds and minerals of interest; Thus, the by-products have been used in bioprocesses that use eco-friendly methods such as aerobic biodegradation, fermentation, hydrolysis and extraction in the case of macroalgae. The products obtained from bioprocesses, depending on their composition of macronutrients, micronutrients, amino acids, microorganisms and bioactive compounds, can be considered as organic fertilizer and/or biostimulant, whose effect ranges from the improvement of growth and development in plants to the control of the biotic and abiotic stress in crops, so that they can grow without difficulties. Organic fertilizers derived from by-products and residual effluents from the fishing industry have adequate macronutrient (N, P and K) and micronutrient (Ca, Mg, S, B, Fe, Cu, Mn, Mo, Zn, and Cl) contents. for plants, as well as peptides and amino acids that are considered as biostimulants. On the other hand, the application of organic fertilizers and biostimulants covers various areas such as horticulture, hydroponics and live food production, the studies found indicated its potential use as a tool to implement organic agriculture and circular economy.